Medication safety improvements during care transitions in an Australian intensive care unit following implementation of an electronic medication management system. (January 2021) - Dabliz, Racha; Poon, Simon K.; Fairbrother, Greg; Ritchie, Angus; Soo, Garry; Burke, Rosemary; Kol, Mark; Ho, Rebecca; Thai, Linh; Laurens, Jacqueline; Ledesma, Sergei; Abu Sardaneh, Arwa; et al.
Highlights: Implementation of an integrated Electronic Medication Management System (EMMS) reduces the risk of medication errors at patient transfer of care from the Intensive Care Unit. However, an integrated EMMS alone doesn't reduce medication errors, workflows need to be optimised accordingly. Workflows that require transcription whether from paper-EMMS to EMMS-to-EMMS increase the risk of errors. The limited customizability of an integrated EMMS in specialized settings such as the ICU can limit innovation and usability. Added safeguards in hospitals such as, pharmacist interventions following implementation of an EMMS could reduce the risk of medication errors and improve patient safety. Abstract: Background: For patients requiring admission to the Intensive Care Unit (ICU), transfers of care (TOC) during admission to and discharge from the ICU are particularly high-risk periods for medication errors. In the Australian setting, commonly general wards and the ICU do not share an integrated Electronic Medical ecord (EMR) and specifically an Electronic Medication Management System (EMMS) as part of the EMR. Purpose: To evaluate the effect of a hospital wide integrated EMMS on medication error rates during ICU admission and at TOC. Method: A 6-month historical control study was performed before and after implementation of the EMMS in the ICU of a tertiary hospital. Prescribing errors detected by pharmacists in the study period were divided into phase 1, (pre-EMMS, 6months), phase 2 (3 months post implementation after shakedown stage) and phase 3 (next 3 months of post implementation). They were categorized as prescribing error types under system or clinical intervention. Chi square statistics and interrupted time series analysis were used to determine if there was significant change in the proportion of patients who had an error at TOC during each phase. Logistics regression was used to determine the relationship between the dependent (error type) and the independent variable (study phase) for errors that occurred during TOC. Results: Errors occurred during TOC in 42 %, 64 % and 19 % of patients in phase 1, 2 and 3 respectively. There was a significant decline in the proportion of patients with an error between phase 1 and 3 (p < 0.01). During a patient's ICU admission, at least one medication error occurred in 28.3 %, 62.6 % and 25.1 % in phase 1, 2 and 3 respectively. Besides procedural errors, the likelihood of an error occurring was greatest in phase 1, compared to phase 2 and 3 across system-related error categories. Conclusion: Medication errors during TOC reduced following implementation of the integrated ICU EMMS. EMMS safety features facilitated reduced system related prescribing errors as well as the severity of errors made.